Detection of Aeromonas hydrophila in Raw Milk and Soft Cheese in Baghdad City - Abdulaal, Nadia Ibrahim (The Iraqi Journal of Veterinary Medicine, 2019)
The frequency and distribution pattern of Aeromonas hydrophilain cow’s raw milk and soft cheese were investigated in Abu-Ghraib, Al-Fudhaliyah and Al-Sadrya regions in Baghdad. A total of one hundred twenty pooled samples were collected during February until June (2019),in which sixty samples of raw milk pooled from milk containers, twenty from each region (four samples collected monthly per region) and sixty samples of fresh soft cheese made from raw unpasteurized milk were collected from different supermarkets in Baghdad as same as proportion above. Modified procedures for isolation and identification were dependent in which, modified tryptone soya yeast extract sheep blood agar supplemented with ampicillin used. Gram stain and oxidase reaction aid in segregation. Modified Congo red assay used to detect biofilm and Kirby-Bauer disc diffusion method was used for determination sensitivity of isolates toampicillin (AM 10µg),cephalexin (CLX, 30µg), azithromycin (AZM, 15µ) andvancomycin (VA 30µg). The results confirmed recovery of eleventh isolates (9.16 %) from one hundred twenty pooled samples, in which four isolates (3.33 %) from raw milk samples; Two (1.66 %) from Abu-Ghraib and one(0.83 %) from each other regions. Seven isolates (5.83 %) were detected from fresh soft cheese samples in which, three (2.5 %) from Abu-Ghraib and two (1.66 %) from each other regions. All isolates were Gram-negative rod- shaped, oxidase positive and biofilm producers. Four isolates (36.36 %) were resistant to selected antibiotics in which, two (18.18 %) from Abu-Ghraib: One (9.09 %) from raw milk and soft cheese; and one (9.09 %) in each other regions in fresh soft cheese only. In conclusions. Milk and cheese production in Abu-Ghraib, Al-Fudhaliyah and Al-Sadrya regions in Baghdad are encountered by the problems of bacterial contamination and presence of multidrug resist strain of A. hydrophila which considered a risk to public health, may be due both insufficient and misuse treatment with antibiotics or in somewhat due to bad quality and/or poor hygiene of processing involved in milk production. Thus recommended monitoring these products for better hygienic status